Peningkatan Kapasitas Santri Pondok Pesantren Entrepreneur Al-Mawaddah Kudus Melalui Pelatihan Web - Muhammad Arifin; R. Rhoedy Setiawan (Universitas Muria Kudus, 2019)
Children are a generation of people's hope in facing and preparing for their future needs attention, given the enormous influence of globalization on their development. For this reason, the presence of various Islamic educational institutions is absolutely necessary. Al-Mawaddah Kudus Entrepreneurs Modern Islamic Boarding School is an educational institution that has been created to foster and prepare young Muslims in welcoming their future, this lodge focuses on developing three aspects, namely intellectual spirituality, entrepreneurship and leadership. In the aspect of entrepreneurship this boarding school provides their students how to entrepreneurship and make a product. The purpose of this Community Service activity is to add insight to the students of the Al-Mawaddah Kudus Modern Islamic Boarding School about the web so that they can use web media to market their products.